Research design and method selection making good choices in the social sciences - Panke, Diana (SAGE Publications, Inc., 2018)
Heavily grounded in helping students make the best choices for their projects, this book explores how to develop and work with theory, research questions, and method selection to build solid, logical proposals and move from research concepts to fully realized designs. The approach that works best for specific research questions - How design choices can affect practice. Perfect for upper undergraduate and postgraduate students, this book will instil confidence and good decision making to ensure constructively informed design and practice.